Grain kernel damage during threshing: a comprehensive review of theories and models - George Ashwehmbom Looh; Fangping Xie; Xiushan Wang; Augustine Ngiejungbwen Looh; Hamdaoui Hind (Journal of Agricultural Engineering)
Grain threshing is aimed at separating the grain from the inedible chaff. However, mechanical forces often damage grains, impacting their quality, market value, and germination ability. This comprehensive review examines theories and models developed to study and predict grain damage during threshing. These include contact theory, fracture mechanics models, discrete element modeling, and finite element analysis. This review delves into how these theories elucidate the influence of grain characteristics, such as moisture content and kernel size, on susceptibility to damage. It assesses how different machine parameters like threshing speed drum design and concave settings contribute to damage such as breakage, fissures, and internal cracks. We delve deeply into utilizing contact theory to estimate stress distribution when metal grains collide, employing fracture mechanics to understand crack initiation and propagation, and utilizing DEM and FEA to simulate how grains move within the thresher. By synthesizing knowledge from these modeling approaches, this review offers an understanding of the multifaceted nature of grain damage during threshing. They emphasize the significance of tuning settings and implementing suitable pre and post-threshing techniques to reduce waste and maintain top-notch grain quality for eating and seeding. This in-depth evaluation offers insights for scientists, engineers, and farming experts dedicated to enhancing the productivity and eco-friendliness of grain cultivation methods.